2013
DOI: 10.1111/dote.12119
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic esophagitis in children with esophageal atresia

Abstract: Eosinophilic esophagitis (EoE) has only rarely been reported in esophageal atresia (EA) patients. A retrospective case analysis of all EA patients born at our center between January 1999 and April 2012 was performed. A total of 113 of patients were identified; 10 patients were excluded as a result of inadequate data. Eighteen patients (17%) were diagnosed with EoE. The average number of eosinophilis was 30/high-power field (HPF) (19/HPF-80/HPF). The median age for diagnosis of EoE was 1 year and 6 months (8 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
113
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(129 citation statements)
references
References 34 publications
6
113
1
9
Order By: Relevance
“…In relation to the clinical presentation, this study found a significantly higher incidence of GERD symptoms, such as vomiting and dysphagia, among patients with EoE compared to those without EoE. 6,18,22 As it is known in EoE, in all series, associated atopy was frequent (Dhaliwal: 50%; Batres: 66%; Gorter: 50%). 3,18,23 A normal endoscopy, linear furrows, edema, and white exudates were described as endoscopic findings.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 59%
See 4 more Smart Citations
“…In relation to the clinical presentation, this study found a significantly higher incidence of GERD symptoms, such as vomiting and dysphagia, among patients with EoE compared to those without EoE. 6,18,22 As it is known in EoE, in all series, associated atopy was frequent (Dhaliwal: 50%; Batres: 66%; Gorter: 50%). 3,18,23 A normal endoscopy, linear furrows, edema, and white exudates were described as endoscopic findings.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 59%
“…6,18,22 As it is known in EoE, in all series, associated atopy was frequent (Dhaliwal: 50%; Batres: 66%; Gorter: 50%). 3,18,23 A normal endoscopy, linear furrows, edema, and white exudates were described as endoscopic findings. 18,21,22 Multiple biopsies of both the proximal and distal parts of the anastomosis are recommended for EoE diagnosis.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 78%
See 3 more Smart Citations